Pengaruh Media Mobile Learning Berbasis Android “ChemOndro” Pada Model Discovery Learning Terhadap Hasil Belajar Peserta Didik Kelas X SMA Negeri 8 Bone (Studi Pada Materi Pokok Larutan Elektrolit dan Nonelektrolit) - Hidayat, Andi Muhammad Ramadhan; Auliah, Army; Anwar, Muhammad (Jurusan Kimia FMIPA UNM, 2021)
This study is a quasi-experimental research that aimed to know the effect of mobile learning “ChemOnDro” android based media in discovery learning to student achievement of class X SMA Negeri 8 Bone on subject matter of electrolyte and nonelectrolyte solution. The study design used is